Penerapan Metode ADaBta dengan Pendekatan TaRL untuk Meningkatkan Kemampuan Literasi Dasar Murid Kelas II SDN Sokowaten - Zulfa, Farah Naila; Rodiyah, Aminatur; Ratnaningsih, Arum; Sulatimah, Sulatimah (Universitas Nusantara PGRI Kediri, 2025)
An important skill that must be possessed and improved by elementary school students is literacy skills. This study is an effort to overcome the problem of low basic literacy skills of students. The purpose of this study was to determine the effectiveness of the ADaBta method with the TaRL approach in improving the basic literacy skills of grade II students of SDN Sokowaten. This study implemented reading, listening, and retelling reading activities by grouping students based on their ability levels. This study used a Classroom Action Research design conducted in two cycles. The results showed that after the implementation of the ADaBta method with the TaRL approach, there was a significant increase in students' basic literacy skills. The biggest changes occurred in students who were initially at the beginner level and letters who managed to move up to a higher level. As many as 20% of students managed to increase from level 1 to level 2, and 13.33% of students from level 2 to level 3. This study concluded that the combination of the ADaBta method with the TaRL approach was effective in improving students' basic literacy skills in grade II of SDN Sokowaten.